Odpowiedź:
(–4) · 7 – (–2) + 2 · (–14) : 7 = -28+4-2 = 30
Szczegółowe wyjaśnienie:
(–3) – (–7) · (–2) – (–6) = 4 razy 2 = 8
(–3) – (–8) + 1 ∙ (–8) – 3 = 5 -8 -2 = - 5
16 : (–8) – 11 – 3 : (–3) = - 2 - 11 + 1 = -12
(–6) : 2 · (–2) + 2 = - 3 razy -2 + 2 = 6 + 2 = 8
5 + (–5) + (–3)² = 9
(–3) · 7 – (–14) : 7 = - 21 + 2 = 23
(–18) : (–6) + (–12) : (–4) = 3 + 3 = 6
(–4) · 2 – (–4) + (–2) · 5 = -2 + 4 - 10 = - 4
(–4) – (–1) · (–4) : (–2) = - 4 - 2 = 2
(–10) + 14 : (–2) = -10 - 2 = -12
5 + (–32) : (–8) ∙ (–2) = 5 + 4 razy (-2) = 5-8 = -3